Permanent health education in the work process of community health workers (Research, Society and Development, 2020)
Objective: to analyze whether permanent health education constitutes a strategy for qualifying the work process of community health workers. Methodology: this study consists of an integrative literature review. Twelve articles were selected for analysis. Results: it was found that the existence of spaces for permanent education is essential to qualify the practice of Community Health Workers as these are considered powerful devices to generate changes in the work process because they are configured as a space for problematizing and building new ways of caring. Conclusion: the adoption of permanent health education with Community Health Workers is essential for the adoption of collaborative, reflective and critical work, enabling better quality health care for the population.